2011
DOI: 10.1210/jc.2011-0233
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Delivery of Insulin to Adipose Tissue and Skeletal Muscle in Obese Women with Postprandial Hyperglycemia

Abstract: Obese subjects with postprandial hyperglycemia need higher circulating insulin levels than lean controls to attain similar interstitial insulin levels in adipose tissue and skeletal muscle, indicating an impaired transfer of insulin across the endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 20 publications
3
27
1
Order By: Relevance
“…Several studies have shown impaired access of insulin to skeletal muscle in obese humans (38,41), yet a recent study using lipid infusion to induce insulin resistance observed no reduction in the transport of insulin across the vessel wall (45). However, this human study did not report actual levels of interstitial insulin but instead reported change from basal.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Several studies have shown impaired access of insulin to skeletal muscle in obese humans (38,41), yet a recent study using lipid infusion to induce insulin resistance observed no reduction in the transport of insulin across the vessel wall (45). However, this human study did not report actual levels of interstitial insulin but instead reported change from basal.…”
mentioning
confidence: 73%
“…We confirmed that there was no change in the time to steady state but also that the insulin concentration in the lymph (as a measure of the interstitial fluid) was not different from healthy animals. In contrast, long-term physiological models of human insulin resistance do show impaired insulin access (41), and obese patients with postprandial hyperglycemia require a higher level of insulin in the plasma to attain similar interstitial insulin levels as those in healthy patients (38). Thus, it is possible that insulin clearance rates in models of insulin resistance are altered to keep the supply of insulin to muscle and other insulin-sensitive tissues at an optimum level.…”
Section: Discussionmentioning
confidence: 99%
“…In obese, non-pregnant individuals, delayed insulin absorption has been associated with large insulin doses and reduced subcutaneous adipose tissue blood flow [31,32]. Sandqvist et al reported impaired transport of insulin from the circulation to both adipose tissue and muscle in obese, insulin-resistant postmenopausal women [33]. Although the distribution of insulin to adipose tissue correlated with factors relevant to insulin resistance, the metabolic impact of impaired insulin delivery was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of data clarifying whether insulin regulates that transport or whether a transendothelial insulin concentration gradient is present in adipose tissue and whether insulin TET limits insulin action in adipose tissue (96).…”
Section: Nutrient and Hormone Transfer Across The Endotheliummentioning
confidence: 99%